Konsep Anti Eco-Slapp dalam Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Nyoman Gede Aditya Jay Medhika; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2022)
There are several weaknesses in the regulation of the Anti Eco-SLAPP concept in Indonesia, which can hinder the implementation of the Anti Eco-SLAPP concept and cause protection for community participation to still have room for criminalization. This study aims to describe the regulation of the anti-Eco-SLAPP concept in Law Number 32 of 2009 concerning Environmental Protection and Management. This type of research is normative law. This study uses a statute approach by examining the laws and regulations. The data used in this study are primary and secondary data. Data analysis was carried out using qualitative analysis. The data that has been analyzed shows that Anti Eco SLAPP has been regulated in Article 66 of the UUPPLH, which emphasizes that every individual who strives for the right to a good and healthy environment cannot be prosecuted criminally or civilly. In operationalizing Article 66 of the PPLH Law, it is hoped that there are four things that must be considered, namely: the requirements for protection and who is the subject being protected as well as the type of Eco-SLAPP action and the requirements for determining Eco-SLAPP. There are several weaknesses in the regulation of the Anti Eco-SLAPP concept in Indonesia, which can hinder the implementation of the Anti Eco-SLAPP concept and cause protection for community participation to still have room for criminalization. This study aims to describe the regulation of the anti-Eco-SLAPP concept in Law Number 32 of 2009 concerning Environmental Protection and Management. This type of research is normative law. This study uses a statute approach by examining the laws and regulations. The data used in this study are primary and secondary data. Data analysis was carried out using qualitative analysis. The data that has been analyzed shows that Anti Eco SLAPP has been regulated in Article 66 of the UUPPLH, which emphasizes that every individual who strives for the right to a good and healthy environment cannot be prosecuted criminally or civilly. In operationalizing Article 66 of the PPLH Law, it is hoped that there are four things that must be considered, namely: the requirements for protection and who is the subject being protected as well as the type of Eco-SLAPP action and the requirements for determining Eco-SLAPP.